If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -3a + 6 = 6a + 4 Reorder the terms: 6 + 6a + -3a = 6a + 4 Combine like terms: 6a + -3a = 3a 6 + 3a = 6a + 4 Reorder the terms: 6 + 3a = 4 + 6a Solving 6 + 3a = 4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 6 + 3a + -6a = 4 + 6a + -6a Combine like terms: 3a + -6a = -3a 6 + -3a = 4 + 6a + -6a Combine like terms: 6a + -6a = 0 6 + -3a = 4 + 0 6 + -3a = 4 Add '-6' to each side of the equation. 6 + -6 + -3a = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -3a = 4 + -6 -3a = 4 + -6 Combine like terms: 4 + -6 = -2 -3a = -2 Divide each side by '-3'. a = 0.6666666667 Simplifying a = 0.6666666667
| 2x+6+2x+6=5x | | 7-5x=-7x+11 | | 7-5x=7x+11 | | 7x-71+2x+125=180 | | 7x+64+7x+18=180 | | 9x+8-5x=4x-7+x | | 8x+27+7x-27=90 | | 8x+27+7x-23=90 | | 2x+31+8x+49=90 | | 2/3x=-14 | | 10x-7+6x+5=36 | | 16-2x=-6x | | 5x+89+2x-7=180 | | 3x+90+6x+45=180 | | x^3+5x^2+6x+30=0 | | 3x+90+6x+45=90 | | 71+6x=80+5x | | x^2y-3xy-x-10=0 | | 7x+14+3x-4=90 | | 3x-12+8x-96=90 | | 4x+30+5x-30=90 | | -(2x^2-2x+2)= | | 4(4bx+y)=15bx-3y | | 6x-52+3x+34=90 | | 6x-52+3x+32=90 | | 2x+19+6x-39=140 | | 0.6x+1.3=5x-2.22 | | 9x+32+9x+4=90 | | 0.05x-3=0.4(x-4) | | 93+7x=98+6x | | 5x+13+3x+33=70 | | 7x-8[8(x+8)-(x-6)]-9= |